2010
DOI: 10.1517/17460441.2010.512037
|View full text |Cite
|
Sign up to set email alerts
|

Rebinding: or why drugs may act longerin vivothan expected from theirin vitrotarget residence time

Abstract: Simulations presented here for the first time suggest that rebinding may increase the duration and even the constancy of the drug's clinical action. Intact cell radioligand dissociation and related ex vivo experiments offer useful indications about a drug's aptitude to experience target rebinding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
94
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(96 citation statements)
references
References 90 publications
1
94
0
1
Order By: Relevance
“…Salmeterol had equal duration of action across all the receptors, despite large differences in affinity. Rebinding to the receptor of salmeterol that had previously partitioned into the membrane and therefore not removed by washing would prolong the apparent receptor residence time and mask changes in the duration of action at the receptor itself (Vauquelin, 2010;Vauquelin and Charlton, 2010;Sykes et al, 2014). This would also apply to previous studies that observed a long duration of action of salmeterol (e.g., Bradshaw et al, 1987;Ball et al, 1991;Coleman et al, 1996).…”
Section: Discussionmentioning
confidence: 91%
“…Salmeterol had equal duration of action across all the receptors, despite large differences in affinity. Rebinding to the receptor of salmeterol that had previously partitioned into the membrane and therefore not removed by washing would prolong the apparent receptor residence time and mask changes in the duration of action at the receptor itself (Vauquelin, 2010;Vauquelin and Charlton, 2010;Sykes et al, 2014). This would also apply to previous studies that observed a long duration of action of salmeterol (e.g., Bradshaw et al, 1987;Ball et al, 1991;Coleman et al, 1996).…”
Section: Discussionmentioning
confidence: 91%
“…rational drug design now becomes clearer; a compound with a high affinity may result from high specific affinity for the receptor site (low value of k off ) or a high K mem (membrane partition coefficient), which results in an increase in the value of k on , or a combination of these two factors. Importantly a drug whose higher affinity can be attributed to a higher K mem value will be present at higher concentrations in biologic membranes, likely contributing to increased compound duration of action (Vauquelin and Charlton, 2010) in part due to an increase in a compounds' apparent k on , which directly affects receptor rebinding (Vauquelin, 2010). However, increasing lipophilicity to increase potency for membraneassociated targets may be detrimental in terms of the overall drug profile being targeted (Lipinski et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…In these experiments, the receptor-containing membranes are preincubated with the radioligand and the dissociation phase is initiated by adding a large excess of (the same or preferentially another) unlabelled drug. This will prevent or at least limit the formation of new radioligandreceptor complexes and/or rebinding phenomena (Vauquelin and Szczuka 2007;Vauquelin and Charlton 2010;Vauquelin 2010). Different variants of this procedure are depicted in Fig.…”
Section: Radioligand Bindingmentioning
confidence: 99%
“…This latter observation is sometimes interpreted in terms of receptor heterogeneity and/or non-competitivity. More information about rebinding phenomena is provided in (Vauquelin and Szczuka 2007;Vauquelin and Charlton 2010;Vauquelin 2010). Methods 3 and 4 start with preincubating the receptors with radioligand, a brief wash (method 3) or no wash (method 4) followed by washout in the presence of receptor-saturating concentration of unlabelled ligand.…”
Section: Radioligand Bindingmentioning
confidence: 99%